2018
DOI: 10.3389/fphar.2018.00180
|View full text |Cite
|
Sign up to set email alerts
|

Araloside C Prevents Hypoxia/Reoxygenation-Induced Endoplasmic Reticulum Stress via Increasing Heat Shock Protein 90 in H9c2 Cardiomyocytes

Abstract: Araloside C (AsC) is a cardioprotective triterpenoid compound that is mainly isolated from Aralia elata. This study aims to determine the effects of AsC on hypoxia-reoxygenation (H/R)-induced apoptosis in H9c2 cardiomyocytes and its underlying mechanisms. Results demonstrated that pretreatment with AsC (12.5 μM) for 12 h significantly suppressed the H/R injury in H9c2 cardiomyocytes, including improving cell viability, attenuating the LDH leakage and preventing cardiomyocyte apoptosis. AsC also inhibited H/R-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
2
18
0
1
Order By: Relevance
“…The present study investigated the effects of H/R on the viability, damage and apoptosis of H9c2 cells. Consistent with a previous study (15), the data revealed that H/R decreased cell viability, increased cell damage and induced cell apoptosis in a time-dependent manner. Cell viability was reduced by ~40% following a 12/6 h hypoxia/reperfusion period.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study investigated the effects of H/R on the viability, damage and apoptosis of H9c2 cells. Consistent with a previous study (15), the data revealed that H/R decreased cell viability, increased cell damage and induced cell apoptosis in a time-dependent manner. Cell viability was reduced by ~40% following a 12/6 h hypoxia/reperfusion period.…”
Section: Discussionsupporting
confidence: 91%
“…The UPR is a defense mechanism directed toward cellular adaptation to alleviate the unfolded protein load; however, prolonged stress is associated with the activation of proapoptotic proteins, such as CHOP (19). A previous study reported that ER stress is increased following H/R treatment (15). Consistent with this study, the present findings indicated that GRP78, ATF6 and CHOP were upregulated in a time-dependent manner following H/R injury.…”
Section: Discussionmentioning
confidence: 98%
“…Our group and several others have reported that TASAES exerts therapeutic effects on myocardial damage [34,35] and atherosclerosis [22,23]. AsC, isolated from TASAES, was also reported to have powerful cardioprotective effects against ischemia-reperfusion injury in our previous study [20,21]. Moreover, we demonstrated that another AsC analogue can protect against ox-LDL-damaged endothelial cell injury via autophagy induction [36], which prompted us to explore whether AsC has antiatherosclerotic effects and determine its protective mechanism.…”
Section: Discussionmentioning
confidence: 79%
“…Seem, which has been widely used in traditional Chinese medicine [19]. Recently, our group reported that AsC alleviated hypoxia/reoxygenation-induced cardiomyocyte apoptosis in vitro [20] and ex vivo [21] studies. Moreover, we found that total saponins of Aralia elata (Miq.)…”
Section: Introductionmentioning
confidence: 99%
“…The molecular chaperone heat shock protein 90 (HSP90) is highly abundant in stress responses (21) and is important for the stability and function of key regulatory kinases such as IRE1 and PERK (7,20,23). PERK interacts with HSP90 via its .…”
Section: Introductionmentioning
confidence: 99%